2016
DOI: 10.1088/1475-7516/2016/08/048
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure constant and habitable planets

Abstract: We use the existence of habitable planets to impose anthropic requirements on the fine structure constant, α. To this effect, we present two considerations that restrict its value to be very near the one observed. The first, that the end product of stellar fusion is iron and not one of its neighboring elements, restricts α −1 to be 145 ± 50. The second, that radiogenic heat in the Earth's interior remains adequately productive for billions of years, restricts it to be 145 ± 9. A connection with the grand unifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…This coincidence was investigated in detail in Reference [45], where it was found that, since the radioactive heat is generated by alpha decays, which are tunneling processes, their lifetime depends exponentially on the fine structure constant (and to a lesser degree on the other parameters). If α were increased to a value of 1{136, all possibly relevant alpha decays would occur with half lives of less than Gyr timescales, and so would have decayed by this point, leaving the Earth cool and stagnant.…”
Section: Does Life Need Plate Tectonics?mentioning
confidence: 99%
“…This coincidence was investigated in detail in Reference [45], where it was found that, since the radioactive heat is generated by alpha decays, which are tunneling processes, their lifetime depends exponentially on the fine structure constant (and to a lesser degree on the other parameters). If α were increased to a value of 1{136, all possibly relevant alpha decays would occur with half lives of less than Gyr timescales, and so would have decayed by this point, leaving the Earth cool and stagnant.…”
Section: Does Life Need Plate Tectonics?mentioning
confidence: 99%
“…For tractability, we note that in [43], when this sum was performed in earnest, the resultant heat resembled a Gaussian which peaked at α " 1{144 at a value 2.7 times our observed heat. This allows us to use a simplified expression…”
Section: Glaciationsmentioning
confidence: 62%
“…Indeed, these two sources of heat are comparable [42]. Given this intriguing fact, along with the high sensitivity of this latter form of heat to the fine structure constant uncovered in [43], it is worth thoroughly investigating the interplay between these two quantities for generic values of the parameters.…”
Section: Glaciationsmentioning
confidence: 99%
“…At the more fundamental level, nuclei themselves must be stable (Section 2). In addition, if habitable planets require particular nuclear structures, such as iron being the most stable nucleus and/or particular types of radioactivity, then even tighter constraints on the fundamental parameters (e.g, α) can be derived [462,463].…”
Section: Planetsmentioning
confidence: 99%